Diagnostic and Management Considerations for the IPAA With Crohn's Disease-Like Features. (19th July 2022) - Akiyama, Shintaro; Dyer, Emma C.; Rubin, David T.
Abstract : BACKGROUND: Patients with ulcerative colitis often develop medically refractory colonic inflammation or colorectal neoplasia, and approximately 10% to 15% of patients require surgery. The most common surgical procedure is a restorative proctocolectomy with IPAA. Even if the preoperative diagnosis is ulcerative colitis, approximately 10% of patients can develop inflammatory pouch conditions resembling a Crohn's disease phenotype. OBJECTIVE: This study aimed to review the diagnostic approach, prognosis, and management of IPAA with Crohn's disease–like features. DATA SOURCES: The data sources include search in electronic databases. STUDY SELECTION: This narrative review included studies focusing on pouches with Crohn's disease–like features. MAIN OUTCOME MEASURES: The main topics in this review included the pathogenesis, risk factors, diagnosis, phenotypes, prognosis, and medications of pouches with Crohn's disease–like features. RESULTS: A diagnostic approach for the pouch conditions resembling a Crohn's disease phenotype should be based on history–taking to evaluate its risk factors and endoscopic assessment of the pouch. Prior disease history and pathology, location of pouch complications, and timing of complications offer clues for the differential diagnosis of this phenotype. We advocate for the more descriptive term "pouch with Crohn's disease–like features" and reserve the term "Crohn's disease of the pouch" for patients who undergo IPAA and have a precolectomy diagnosis of Crohn's disease or whose colectomy pathology revealed Crohn's disease. Medications, which are often used for traditional Crohn's disease, show efficacy in pouches with Crohn's disease–like features as well. The poor prognosis associated with pouches with Crohn's disease–like features, particularly the fistulizing phenotype, underscores the importance of proactive monitoring and therapeutic intervention. LIMITATIONS: The limitations include no explicit criteria for article selection. CONCLUSIONS: This review suggests future research should seek to understand the natural history and meaningful shorter and longer term therapeutic targets for these types of pouch phenotypes. Long-term follow-up and prospective preoperative and postoperative interventional trials of treatments and prevention strategies are needed.